2017
DOI: 10.1590/s0100-736x2017001100019
|View full text |Cite
|
Sign up to set email alerts
|

Doenças micóticas em gatos no Rio Grande do Sul

Abstract: RESUMO.-As enfermidades fúngicas são diagnósticos diferenciais de diversas morbidades de caráter infeccioso, degenerativo ou proliferativo neoplásico, principalmente em gatos, que é a espécie mais suscetível a estas. Este trabalho descreve os achados anatomopatológicos de doenças fúngi-cas em gatos no período de janeiro de 2005 a dezembro de 2015 pelo SPV-UFRGS. Foram revisados 1.274 protocolos de necropsia e encontrou-se 17 casos de micoses, correspondendo a 1,33% dos diagnósticos. Quanto às amostras provenie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 30 publications
2
8
0
6
Order By: Relevance
“…The increased volume of the popliteal lymph nodes observed in the physical examination may be a nonspecific alteration, because although lymphadenomegaly is present in Cryptococcus spp., infections, the lymph nodes that are usually affected are the mandibular lymph nodes [3]. Hematological and biochemical findings were also non-specific in this study, as has been reported by Marcasso et al [9] who described cryptococcosis in dogs.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…The increased volume of the popliteal lymph nodes observed in the physical examination may be a nonspecific alteration, because although lymphadenomegaly is present in Cryptococcus spp., infections, the lymph nodes that are usually affected are the mandibular lymph nodes [3]. Hematological and biochemical findings were also non-specific in this study, as has been reported by Marcasso et al [9] who described cryptococcosis in dogs.…”
Section: Discussionsupporting
confidence: 62%
“…Nevertheless, due to the macroscopic characteristics observed, rhinosporidiosis and histoplasmosis were considered as differential diagnosis. The literature indicates that other diseases may also be considered as differential diagnosis, such as coccidioidomycosis, blastomycosis, neoplasias [9,10], such as squamous cell carcinoma [3,4]. The observed similarity between the lesions present in these different diseases can lead to underdiagnoses of cryptococcosis in the clinical setting [9].…”
Section: Discussionmentioning
confidence: 99%
“…Um apresentando feridas ulceradas em cabeça, pescoço, região periorbital, comissura labial e membros, e outro apresentando lesão em dígito do membro pélvico esquerdo. Já em estudo retrospectivo de doenças micóticas em gatos realizado por Castro et al (2017), em 13 gatos com criptococose confirmada, oito apresentaram sinais clínicos cutâneos como nódulos, ulcerações e exsudação serossanguinolenta, esta última compatível com o conteúdo do abscesso da paciente relatada.…”
Section: Discussionunclassified
“…A dificuldade na formulação de um diagnóstico sugestivo de criptococose pode estar diretamente associada à presença de sinais clínicos inespecíficos, diversidade na sua apresentação clínica e distribuição das lesões (Pereira et al, 2013;Trindade et al, 2008) como observado em outros trabalhos (Castro et al, 2017;Galiza et al, 2014). Em estudo realizado por Galiza et al (2014), somente em dois de seis gatos houve suspeita clínica de criptococose.…”
Section: Discussionunclassified
See 1 more Smart Citation